Simplified pipelines for genetic engineering of mammalian embryos by CRISPR-Cas9 electroporation†. Issue 1 (26th April 2019) - Miao, Deqiang; Giassetti, Mariana Ianello; Ciccarelli, Michela; Lopez-Biladeau, Blanca; Oatley, Jon M
Abstract: Gene editing technologies, such as CRISPR-Cas9, have important applications in mammalian embryos for generating novel animal models in biomedical research and lines of livestock with enhanced production traits. However, the lack of methods for efficient introduction of gene editing reagents into zygotes of various species and the need for surgical embryo transfer in mice have been technical barriers of widespread use. Here, we described methodologies that overcome these limitations for embryos of mice, cattle, and pigs. Using mutation of the Nanos2 gene as a readout, we refined electroporation parameters with preassembled sgRNA-Cas9 RNPs for zygotes of all three species without the need for zona pellucida dissolution that led to high-efficiency INDEL edits. In addition, we optimized culture conditions to support maturation from zygote to the multicellular stage for all three species that generates embryos ready for transfer to produce gene-edited animals. Moreover, for mice, we devised a nonsurgical embryo transfer method that yields offspring at an efficiency comparable to conventional surgical approaches. Collectively, outcomes of these studies provide simplified pipelines for CRISPR-Cas9-based gene editing that are applicable in a variety of mammalian species. Abstract : Efficient gene editing in mouse, pig, and cattle embryos by delivery of CRISPR-Cas9 reagents with electroporation.